“There Always Is A Possibility Not To Submit” - Rickevičiūtė, Kristina (Problemos, 1996)
The present publication presents to the reader some excerpts from the letters of Kristina Rickevičiūtė (1922-1984), an associate professor of the Department of Logic and History of Philosophy at Vilnius University, a student of the well-known philosopher Vasyli Seseman (1884-1963). The letters reflect the author’s philosophical mind and her attitude towards life. They are addressed to K. Rickevičiūtė’s friend Genovaitė Gustaitė, a historian. In her article written also in a letter form, G. Gustaitė characterizes the personality of K. Rickevičiūtė and speaks of her contribution to the development of philosophical culture in Lithuania.